"A Strange Chaos": Preserving Internet Art in the Wake of Walter Benjamin's Critical Legacy. - Boxer, Carly B. (Tufts Archival Research Center, 2005)
This thesis explores current approaches to preserving Internet art, and examines comparisons made between Internet art and earlier media from a theoretical perspective. Contemporary preservation implicitly accepts as true twentieth-century literary critic Walter Benjamin's contention that the mechanically reproduced work of art loses its aura and falls victim to ideological objectives: in so doing, the work risks inauthenticity, both in the experience it provides its viewer and in its function within a larger ideological system. The works that Internet art are associated with retain medium-specific elements; they value display materials from a work's first exhibition, they prioritize an original' performance, they ascribe value to the unadulterated display of an individual artist's aesthetic tendencies, and they are exhibited within a gallery or museum. These traits allow curators and conservators to legitimately assert the existence of some authentic' work that can be experienced and preserved. Internet art, however, demonstrates none of these characteristics. This thesis argues that current suggested practices for preserving Internet art and the frequent comparisons made between Internet art, variable media art, and performance ignore those characteristics most central to Internet art's eponymous medium: its place outside the walls of the traditional museum, its ability to exist in infinite iterations with no original' taking priority, its unusual relationship to time, and the ways in which it shatters expectations of single authorship.